Organizational Effectiveness of The Indonesia Halal Industrial Estate - Yazid, Muhammad; Ismatul Khayati; Prasetyo, Aji (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
Halal Industrial Estates were built in Indonesia for the purpose of making Indonesia the center of the world's halal destinations. Halal Industrial Estates that have received licenses include the Halal Industrial Park Sidoarjo (HIPS), East Java. HIPS has only been operating for 3 years. As one of the industrial estates that focuses on MSME business investors, HIPS deserves the spotlight of this research regarding the extent of organizational effectiveness that has been implemented. On the one hand, HIPS has been able to demonstrate its organizational effectiveness by obtaining business actors who invest in the area. Products produced by business actors in the HIPS area can be guaranteed halal because from the beginning of entering the area they must be halal certified. Although indeed the quantity of investors in HIPS has not been maximized to make HIPS the main barometer of Indonesia's halal destinations in the eyes of the world.